Task- and Time-Dependent Memory Enhancement by Dehydroepiandosterone in Day-Old Chicks - A. N. B. Johnston; P. V. Migues (Neural Plasticity)
We have previously reported the presence of dehydroepiandosterone (DHEA) in the dayold- chick brain, and a role for it in enhanced memory formation. Here we confirm that intracerebral injections of DHEA 5 min before training on the weak passive avoidance task enhanced recall 24 hours after training. Recall per se on an appetitive visual categorization task was not altered by administration of DHEA 5 min before training. However administration of DHEA 5 min before limited or very limited training on a visual categorization task (20 or 10 pecks only) appeared to enhance consolidation of this task at test 24 h after training; reducing the latency and total time taken to complete the test (60 pecks), while not detrimentally altering accuracy. Moreover, DHEA is unlikely to induce this effect via possible anxiolytic effects because it did not alter behavior in the open field test. We also examined diffusion of DHEA throughout the brain at various stages following intracerebral injection.